2006
DOI: 10.1007/s11270-005-9035-4
|View full text |Cite
|
Sign up to set email alerts
|

Coastal Pollution and Potential Biomonitors of Metals in Mauritius

Abstract: Contaminant metals are potentially toxic, accumulate in the sediment, are bioconcentrated by organisms and may cause health problems to humans via the food chain. Discharge of industrial wastewaters and untreated sewage pose a particularly serious threat to the coastal environment of Mauritius, but very little information exists on contaminant metals. This study aimed principally to assess such contamination by (i) reviewing available data, (ii) examining the results of metal (Cd, Cu, Cr, Pb and Zn) analysis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 51 publications
0
14
1
2
Order By: Relevance
“…The nearshore marine ecosystem is a dynamic environment that could be impacted by such activities. Coastal waters and sediments adjacent to the major urban areas, in particular, can be heavily influenced (Daby, 2006). A high-resolution long-term time series of studies offers a reliable approach to study the impact of human activities on coastal water (Badran, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The nearshore marine ecosystem is a dynamic environment that could be impacted by such activities. Coastal waters and sediments adjacent to the major urban areas, in particular, can be heavily influenced (Daby, 2006). A high-resolution long-term time series of studies offers a reliable approach to study the impact of human activities on coastal water (Badran, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, macroalgae have been increasingly used as a tool for monitoring marine environments contaminated by heavy metals (Daka et al, 2003;Stengel et al, 2004;Daby, 2006, Baumann et al, 2009Kumar et al, 2009;Tonon et al, 2011). Many macroalgae are able to accumulate high levels of trace metals, which are sometimes larger than those found in water samples from the same site (Cardwell et al, 2002;Salgado et al, 2006).…”
Section: Bioremediationmentioning
confidence: 99%
“…The aquatic environment in Mauritius is mainly affected by heavy metals contamination arising from industrial wastes and contaminated sewage wastewater [2]. Furthermore, it was reported that regions close to Grand River North West were contaminated with Cu, Pb, and Zn emerging from vehicles dust and galvanized signs or other equipment found on roads nearby [3].…”
Section: Introductionmentioning
confidence: 99%